Measuring mental health: a new tool and its usefulness - MW Gunatunga (College of Community Physicians of Sri Lanka, 2012)
Introduction It has been shown that a variety of mental health states, such as anger, insatiability and lack of concentration which are not clinically diagnosable disease entities can occur among "normal‟ individuals. Outcomes of those mental states such as violence, abuse, suicide and accidents have become a considerable health and socioeconomic burden. Before designing interventions for mental health promotion and prevention of undesirable effects of poor mental health, the status of mental health of "normal" individuals needs to be measured. Tools available for this purpose are scarce. The present study was undertaken to identify variables constituting mental health and to develop and validate a tool to measure mental health among apparently healthy individuals. Methodology Variables constituting mental health were identified by a panel of experts and "Primary Mental Health Questionnaire" was developed. Content and consensual validity of the questionnaire were tested. Construct validity was tested against 100 qualitative in-depth interviews. It was administered on a representative sample of 447 residents to assess its usefulness and acceptability as a self-administered survey tool. Results: The questionnaire included a section on socio-demographic information and a section to assess mental health status. The panel of experts agreed on content and consensual validity. Paired sample correlation co-efficient for construct validity varied from 0.19 to 0.54 and were significant (p<0.05). The questionnaire was understood well and accepted by all population groups on which it was administered. There was a response rate of more than 95% in the population survey. Conclusions Results warrant use of this tool, in its present form. Further validation and improvements will make this questionnaire more meaningful and useful for epidemiological and clinical surveys. DOI: http://dx.doi.org/10.4038/jccpsl.v15i1.4935 Journal of the College of Community Physicians of Sri Lanka Vol.15(1) May 2010 13-23